Effects of Extracorporeal Magnetic Wave Pelvic Floor Therapy Combined with PFMT on Pelvic Floor Muscle Strength and Pelvic Organ Prolapse in Patients with Postpartum Pelvic Floor Dysfunction: A Prospective Randomized Trial - Jinghui Xu; Zhihua Shi; Yan Chen (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: To investigate the effect of extracorporeal magnetic wave pelvic floor therapy combined with pelvic floor muscle training (PFMT) on pelvic floor muscle strength and the degree of pelvic organ prolapse in patients with postpartum pelvic floor dysfunction. Methods: A total of 100 patients with postpartum pelvic floor dysfunction (PFD) who were treated in Lishui People’s Hospital from January 2020 to May 2022 were selected as the research objects. According to the random number table method, they were divided into a control group of 50 cases and an observation group of 50 cases. The control group received pelvic floor muscle training, and the observation group received extracorporeal magnetic wave pelvic floor therapy combined with PFMT on its basis, and the two groups received continuous treatment for 8 weeks. The clinical efficacy; Pelvic floor muscle strength classification; Pelvic organ prolapse quantitative scale (POP-Q) score Ap and C index points; Pelvic floor dysfunction questionnaire (PFDI-20) and Pelvic floor dysfunction questionnaire (PFIQ-7) score were compared between the two groups. Results: Compared with the control group (70.00%), the total clinical effective rate (96.00%) of the observation group was significantly increased (p < 0.05); compared with before treatment, the proportion of pelvic floor muscle strength of grade 0 in the observation group was significantly decreased, and the proportion of grade Ⅳ was significantly increased after treatment, and the proportion of pelvic floor muscle strength of grade 0 in the observation group was significantly lower than that in the control group, and the proportion of grade Ⅳ was significantly higher than that in the control group (p < 0.05); Compared with before treatment, the POP-Q scores Ap and C index points in the two groups were significantly decreased after treatment, and the POP-Q scores Ap and C index points in the observation group were significantly lower than those in the control group (p < 0.05); Compared with before treatment, the PFDI-20 scores and PFIQ-7 scores in the two groups after treatment were significantly decreased, and the PFDI-20 scores and PFIQ-7 scores in the observation group were significantly lower than those in the control group (p < 0.05). Conclusions: Extracorporeal magnetic wave pelvic floor therapy combined with PFMT can effectively improve the clinical efficacy of PFD patients, improve pelvic floor muscle strength, reduce the degree of pelvic organ prolapse, and improve the quality of life of patients, which has a high clinical reference value. Clinical Trial Registration: The study was registered at https://www.chictr.org.cn (registration number ChiCTR1900024783).